Research progress on the applications of paper chips. Issue 15 (26th February 2021) - Tong, Xin; Ga, Lu; Zhao, Ruiguo; Ai, Jun
Abstract : Due to the modern pursuit of the quality of life, science and technology have rapidly developed, resulting in higher requirements for various detection methods based on analytical technology. Abstract : Due to the modern pursuit of the quality of life, science and technology have rapidly developed, resulting in higher requirements for various detection methods based on analytical technology. Herein, the development, fabrication, detection and application of paper-based microfluidic chips (μPAD) are summarized. We aim to provide a comprehensive understanding of paper chips, and then discuss challenges and future prospects in this field.